2012
DOI: 10.1021/nl203512c
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetism in Graphene Nanoribbons: Split versus Oxidative Unzipped Ribbons

Abstract: * These authors contributed equally to this workTwo types of graphene nanoribbons: (a) potassium-split graphene nanoribbons (GNRs), and (b) oxidative unzipped and chemically converted graphene nanoribbons (CCGNRs) were investigated for their magnetic properties using the combination of static magnetization and electron spin resonance measurements. The two types of ribbons possess remarkably different magnetic properties. While the low temperature ferromagnet-like feature is observed in both types of ribbons, s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
77
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 51 publications
14
77
2
Order By: Relevance
“…From the exchange bias variation, a maximum value of H E ~ 52 Oe is observed when the GNRs were cooled with negative field of 1 kOe. On the other hand, previously, a maximum H E of 40 Oe has been observed upon cooling the GNRs with a positive field value of 4 kOe [19]. Our results are in accordance with the work done by Wu et.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…From the exchange bias variation, a maximum value of H E ~ 52 Oe is observed when the GNRs were cooled with negative field of 1 kOe. On the other hand, previously, a maximum H E of 40 Oe has been observed upon cooling the GNRs with a positive field value of 4 kOe [19]. Our results are in accordance with the work done by Wu et.…”
Section: Resultssupporting
confidence: 94%
“…In our earlier work [19], we have reported that the low temperature susceptibility of the GNRs exhibits a peak at 70 K under the zero field conditions (ZFC), such a broad maximum has been correlated to the competing interaction between various FM and AFM magnetic phases. Such competing interactions lead to a negative EB upon positive field cooling.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In analogy to our earlier HYSCORE work 38 on other GNRs, in addition to the proton hf interactions, the HYSCORE 13 C signals (in natural abundance) at low frequencies in Fig. 6 indicate 13 C hfc's are in the range |A( 13 C)| < 4 MHz (≈0.14 mT).…”
Section: Resultssupporting
confidence: 71%
“…31 Additional evidence is coming from magnetization and electron spin resonance experiments on unzipped graphene ribbons. 32 The sublattice degree of freedom plays a central role in the magnetic properties of bipartite lattices. [33][34][35] Very much like an external magnetic field favors one spin orientation and splits the spin states, an external perturbation favors one sublattice with respect to the other and opens a gap in the band structure of graphene.…”
Section: Introductionmentioning
confidence: 99%